A "New" Tool For Cardiopulmonary Monitorization in Icu in Daily Practice: Transthoracic Echocardiography and Lung Ultrasound - Gülay Eren; Oya Hergünsel; Zafer Çukurova; Yüksel Doğan; Osman Karakaya (Galenos Yayinevi, 2012)
Objective: We aim at looking over our experiences in order to prove the use of transthoracic echocardiography and lung ultrasonography for monitorization of treatment of patients in intensive care. Material and Method: 18 patients in intensive care unit were examined echocardiographically by an intensivist and a cardiologist evaluated these transthoracic echocardiography (TTE) visions for image quality and reliability. Demographic and clinical data of patients, clinical prognosis, acustic windows used for imaging, echocardiographical findings and contribution of these findings to clinical progress evaluated by a 4-scale all were recorded and evaluated.baseline within 72 hours after administration of contrast agent. Results: 18 patients were evaluated by 21 TTE images and 2 lung ultrasonography. This imaging provided adequate and valuable data for 94.3% of cases. In 38.8% of cases TTE images were supportive for the present data, whereas it provided new data in 33.3% and data contributing the diagnosis and leading to definitive treatment in 22.2%. Recorded TTE images were scored by the cardiologist and none of them were evaluated as imaging quality unevaluable. Both lung ultrasounds provided valuable data to the management of patients. Conclusion: Ultrasonography (both TTE and lung ultrasound) is a safe, noninvasive bedside tool to provide valuable contribution to the management of critical cases in intensive care unit. (Journal of the Turkish Society Intensive Care 2012; 10: 13-9)